Dual Band Double Cross Monopole Antenna with Defected Ground Structure - Madhavi, B; V Siva Prasad, M (International Journal of Engineering and Technology, 2018)
A twofold band deceive monopole recieving wire is outlined with absconded ground structure. The planned radio wire is created on FR4 substrate of thickness 1.6 mm and dielectric consistent 4.4. the proposed reception apparatus is working in double band at 3 GHz (2.5-3.5 GHz with data transfer capacity of 1 GHz) and 9 GHz (8.5-9.5 GHz with transmission capacity of 1 GHz). The general measurement of this position of safety recieving wire is around 35x25x1.6 mm. Radio wire giving pinnacle pick up of in excess of 4.6 dB at 3 GHz and 3.86 dB at 9 GHz. The prototyped configuration was estimated with aniritsu combinational analyzer and the acquired outcomes are demonstrating great coordinating with reproduction results got from HFSS instrument. Â Â